Edukasi Pemanfaatan Limbah Rumah Tangga Sebagai Pupuk Organik Cair bagi Petani - Nisdianti, Aprilia; Zurba, Nabil; Rahmi, Mira Mauliza; Lisdayanti, Eka; Qausar, Haves (Lok Seva: Journal of Contemporary Community Service, 2024)
The reluctance of the community to dispose of waste at the Final Disposal Site (TPA) becomes an obstacle to effective urban waste management. The accumulation of waste over time can lead to water pollution problems. One waste management method is composting. Compost is a biodegradable substance that can retain moisture while decomposing in the air and under sunlight. The basic principle of composting technology is based on the natural decomposition process of organic materials. To address this issue, Liquid Organic Fertilizer (POC) can be used. POC is a liquid fertilizer made from various organic materials, such as plants and food scraps. Waste and residues in the body will decompose anaerobically (without oxygen) without the help of sunlight. This activity was carried out at the Pohroh City Hall, Meureudu Subdistrict, Pidie Jaya Regency, on June 8, 2023. The program aims to educate the surrounding community that household waste, such as vegetable waste and rice washing water, can be utilized as liquid fertilizer, which plays an important role in tree planting. This community service was conducted at the Pohroh Village Hall, Meureudu Subdistrict, Pidie Jaya Regency. The production of liquid organic fertilizer (POC) from household waste begins with making a sample using simple tools and materials, such as a bucket, sieve, 1.5-liter mineral water bottle, sugar, rice washing water, vegetable/fruit waste water, and EM4. The success of POC production can be seen from the presence of white spots on the surface, a yellow-brown color, and a scent resembling fermented rice, but without a foul odor. Through education on household waste management, it is hoped that it will increase the community's knowledge, understanding, and innovation in managing household waste.